Pengaruh stres kerja, kepuasan kerja dan job insecurity dimasa pandemi covid-19 terhadap turnover intention karyawan - afina ulfi rizqi; Sutrisno; Ira Setiawati (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2022)
This study aims to determine the effect of job stress, job satisfaction and job insecurity on the turnover intention of employees of PT. Delta Dunia Clothing Textiles Demak . Respondents in this study were employees of PT. Delta Dunia Sandang Tekstil Demak with a sample of 290 employees. The data collection process was carried out by distributing questionnaires through the media google form and manual paper to all employees of PT. Delta Dunia Clothing Textile Demak. This research uses quantitative methods. The data collection method used a simple sampling. This study uses multiple linear regression analysis using statistical test tools. The data processing of this research uses the IBM SPSS 24 tool. The results of this study indicate that there is a positive and significant effect between job stress on turnover intention, and job satisfaction has a negative and significant effect on turnover intention and job insecurity has a positive and significant effect on turnover intention. Job stress, job satisfaction and job insecurity together have a positive and significant effect on turnover intention. The regression equation obtained is Y = 12,523. Job stress has a positive effect of 0,353 on turnover intention, job satisfaction has a negative effect of -0,087 and job insecurity has a positive effect of 0,239. Based on the results of the research that has been done, the Adjusted R Square value is 0.819 or 82.9%. This shows that the variable turnover intention can be explained by the variables of job stress, job satisfaction and job insecurity, which is 82.9%, while the remaining 0.181 or 18.1% is influenced by other variables not examined in this study.